N-acetylcysteine alleviates PCB52-induced hepatotoxicity by repressing oxidative stress and inflammatory responses - Zhou, Wen-Tao; Wang, Li-Bin; Yu, Hao; Zhang, Kai-Kai; Chen, Li-Jian; Wang, Qi; Xie, Xiao-Li (PeerJ, 2020)
Polychlorinated biphenyls (PCBs), particularly low chlorinated congeners in our environment, can induce human hepatotoxicity. However, the mechanisms by which PCBs cause hepatotoxicity remain elusive. Moreover, there are no effective treatments for this condition. In this study, 40 μM PCB52 was administered to rat (Brl-3A) and human hepatocytes (L-02) for 48 h following the N-acetylcysteine (NAC)/saline pretreatment. A significant decrease in cell viability was observed in PCB52-treated cells relative to the control. Besides, PCB52 significantly increased reactive oxygen species (ROS) levels and malondialdehyde (MDA) contents, suggesting induction of oxidative stress. The expression of Traf6, MyD88, and Tnf in Brl-3A cells and that of MYD88, TNF, and IL1B in L-02 cells were significantly upregulated by PCB52. Consistently, overexpression of TLR4, MyD88, Traf6, and NF-κB p65 proteins was observed in PCB52-treated cells, indicating activation of inflammatory responses. Nevertheless, no changes in kelch-like ECH-associated protein 1 (keap1), nuclear factor-erythroid 2-related factor (nrf2), and heme oxygenase-1 proteins were observed in PCB52-treated cells, indicating non-activation of the keap1/nrf2 pathway. Pretreatment with NAC significantly ameliorated PCB52 effects on cell viability, ROS levels, MDA contents and expression of inflammatory elements at both RNA and protein levels. However, no changes in keap1, nrf2 and HO-1 protein levels were detected following NAC pretreatment. Taken together, with non-activated keap1/nrf2 pathway, PCB52-induced oxidative stress and inflammatory responses could be responsible for its hepatotoxicity. These effects were effectively attenuated by NAC pretreatment, which scavenges ROS and dampens inflammatory responses. This study might provide novel strategies for the treatment of the PCBs-associated hepatotoxic effects.
Keywords: N-acetylcysteine; PCB52; Hepatotoxicity; Oxidative stress; Inflammatory response